Keefektifan Model Group Investigation Berbantuan Media Kartu Truth Or Dare “Inkara” Terhadap Hasil Belajar IPAS Kelas V SD 3 Wergu Wetan - Hastiani, Eigi Pema; Masfuah, Siti; Kironoratri, Lintang (Edukasi: Jurnal Penelitian dan Artikel Pendidikan, 2024)
The learning outcomes of elementary school students tend to be low due to the lack of innovation in the learning process, including the use of models and media that can encourage active student participation. This study aims to determine the difference in the average between students' pretest and posttest scores before and after learning using the Group Investigation model assisted by Truth Or Dare Card media on the learning outcomes of fifth grade students of SD 3 Wergu Wetan, and analyze the increase in students' pretest and posttest scores before and after learning using the Group Investigation model assisted by Truth Or Dare Card media on the learning outcomes of fifth grade students of SD 3 Wergu Wetan. This study uses a quantitative pre-experimental approach and one group pretest-posttest. The study population consisted of 27 fifth grade students. This study uses a saturated sampling technique, so that all members of the population are sampled. The data in this study were obtained through observation, interviews, documentation, and tests. Data analysis in this study used the normality test, paired sample t-test and n-gain test. Based on the results of the study, it was obtained that based on the paired sample t-test, the t-count value was obtained at 24.437 with a significance value (2-tailed) of 0.000 <0.05, this indicates that Ho is rejected and Ha is accepted. Meanwhile, in the N-Gain test, the score obtained was 0.6273 with a moderate category and an increase in the average N-Nain percentage of 62.7267%. Based on this analysis, it can be concluded that the Group Investigation learning model supported by the Truth Or Dare Card media has an effect on the learning outcomes of the Indonesian Kaya Raya material for grade V elementary school students. Based on the N-Gain results, it was also obtained that the Group Investigation learning model assisted by the Truth Or Dare Card media can improve the learning outcomes of the Indonesian Kaya Raya material.